2006
DOI: 10.1080/10810730600614110
|View full text |Cite
|
Sign up to set email alerts
|

The Health Buck Stops Where? Thematic Framing of Health Discourse to Understand the Context for CVD Prevention

Abstract: Using a constructed week methodology, we analyzed media summaries for the type of health discourse (health care delivery, disease-specific prevention, lifestyle risk factors, public/environmental health disease, social determinants of health) portrayed over a 5-year period as a means of describing the context within which health staff worked to prevent heart disease in one Canadian province. The results reveal that heart disease received very little media coverage, despite provincial health data revealing it t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
37
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 44 publications
1
37
0
Order By: Relevance
“…A search on Factiva for Australian news items published in five major Australian daily newspapers containing the word 'obesity' found that the volume of coverage had risen from 67 in 1996 to 1416items in 2006(Personal communication, CMF Bonfiglioli, 27 June 2007. A study of US news on this topic found a greater than fourfold increase (Kim and Willis 2007), and an examination of 5 years of news coverage in one Canadian province found that reporting of physical activity, nutrition, and obesity combined overtook coverage of tobacco in 2003 (Wharf Higgins et al 2006). While our study did not permit direct comparison of the volume of each, we observed that tobacco issues have continued to be newsworthy up until 2006, and up until 2005 they had a consistent prominence.…”
Section: Changes In News Coverage Over Timementioning
confidence: 46%
“…A search on Factiva for Australian news items published in five major Australian daily newspapers containing the word 'obesity' found that the volume of coverage had risen from 67 in 1996 to 1416items in 2006(Personal communication, CMF Bonfiglioli, 27 June 2007. A study of US news on this topic found a greater than fourfold increase (Kim and Willis 2007), and an examination of 5 years of news coverage in one Canadian province found that reporting of physical activity, nutrition, and obesity combined overtook coverage of tobacco in 2003 (Wharf Higgins et al 2006). While our study did not permit direct comparison of the volume of each, we observed that tobacco issues have continued to be newsworthy up until 2006, and up until 2005 they had a consistent prominence.…”
Section: Changes In News Coverage Over Timementioning
confidence: 46%
“…Gruhn and Hawkins (2004) described a successful collaborative program involving journalism educators, newspaper publishers, and a private funding agency seeking to accomplish that goal by encouraging the adoption of a public health frame in reporting children's health problems. Higgins et al (2006) recommended that health advocates take better advantage of media outlets to press their messages. After Men's Health magazine identified Houston as the "Fattest City in the U.S.," Houston mayor Bill White organized the "Get Moving Houston" fitness campaign in 2005 (www.getmovingHouston.com).…”
Section: Discussionmentioning
confidence: 99%
“…Kim, Scheufele, and Shanahan (2002) referred to frames as "easy-to-understand interpretive packages" (p. 8) that lead audience members to draw different conclusions about causality or responsibility based on the same or very similar factual content. Higgins, Naylor, Berry, O'Connor, and McLean (2006) echoed this sentiment in their contention that through framing employed in news stories, "Media are key sources in defining importance and relevancy of health issues giving meaning to health issues and shaping public perceptions of who is responsible for solutions and hence . .…”
mentioning
confidence: 92%
See 2 more Smart Citations